Tratamiento para efluvio telógeno mediante la técnica de mesoterapia capilar con centella asiática en paciente masculino de 50 años - Angueta Ramos, Juslady Micaela (2025)
The purpose of this project was to focus on a treatment for telogen effluvium using the technique of capillary mesotherapy with Asiatic Centella in a 50-year-old male patient. The objective was to evaluate the efficacy and safety of this method as a treatment for telogen effluvium, assess the patient's condition, and present the evolution of the results of the application of this procedure. The idea to be defended is that with the appropriate application of the mesotherapy technique using Asiatic Centella as an active ingredient, its effectiveness and reliability can be determined. The results should allow for hair strengthening, identifying the hair porosity that indicates it absorbs hydration easily, and observing whether the amount of hair maintained or even increased slightly. Additionally, important aspects were explored, such as considering that in treating telogen effluvium, and when diagnosed as chronic-acute effluvium, it may not be completely eliminated, nevertheless, the positive data and evidence earlier mentioned were recorded. Therefore, this project aims to contribute to scientific and investigative knowledge regarding the benefits of Asiatic Centella, with its properties and effects in improving blood circulation in the scalp and strengthening blood vessels and hair follicles through the mesotherapy technique. These results were obtained using essential tools such as a capillary diagnosis file and a follow-up record, allowing the patient to observe the evolution and improvement in their hair condition.